MOLECULAR ABSORPTION BANDS IN JUPITER TROPOSPHERE RESEARCH - Vdovichenko, V.D.; Karimov, A.M.; Kirienko, G.A.; Lysenko, P.G.; Teifel, V.G.; Filippov, V.A.; Kharitonova, G.A.; Hogenez, A.P. (Academic Scientific Journal of Computer Science, 2020)
Based on spectrophotometric observations of Jupiter, made since 2004, some features of the behavior of the methane and ammonia absorption bands on the planet's disk, are discussed. In the meridional course of the observed variations in the equivalent widths of both ammonia and methane in the 6000A - 8000A spectral range, there are both similar elements and differences. Variations in the equivalent widths of ammonia absorption bands at 6450 Å and 7870A show a decrease in absorption in the low and moderate latitudes of the northern hemisphere. In the 7870 Å band, compared to the 6450 Å band, the ammonia absorption depression in the region of the Northern Equatorial Belt is narrower in latitudes and some more deeper. With similar latitudinal variations in methane absorption, systematic differences are observed in the position of extrema for different bands of ammonia and methane. The importance of studying the behavior of absorption bands for optical probing of the troposphere of Jupiter is noted. The alternatives of the model of the troposphere structure and ammonia cloud on Jupiter are discussed. The first model assumes the existence of a geometrically and optically thick ammonia cloud layer. In this layer, the formation of the observed molecular absorption bands in the process of multiple scattering mainly occurs. An alternative model assumes the presence of a geometrically and optically thin layer of ammonia clouds. The bulk of the molecular absorption in this case is created in the troposphere between the cloud layers of ammonia and ammonium hydrosulfide. The need for further research in this direction is noted. One of the important results, so far preliminary, was the differences we found in the latitudinal position of the extremes of the intensities of the molecular absorption bands on Jupiter. This feature is most likely due to the difference in the conditions of formation of different absorption bands in the ammonia cloud layer and the underlying troposphere. The complexity and ambiguity of the mechanism of formation of molecular absorption bands requires further consideration of both various models of the structure of the Jovian atmosphere and further detailed spectral observations of Jupiter, with particular emphasis on the study of weak and moderate absorption bands, which we would like to draw attention to in this publication